Co-creation of a massive open online course: An exploration of the motives and motive fulfillment of a faculty member and student co-instructors - Bressler, Alison; Quintana, Rebecca M.; Zint, Michaela (Frontiers in Education, 2022)
We present a case study of a “by learners, for learners” approach to the co-design of a massive open online course (MOOC), on climate change. To learn about the motivations of a faculty member and students who participated in this process, we collected data through focus groups, interviews, and questionnaires. Three main motivations emerged: (1) The faculty member and student co-instructors sought to create accessible and practical resources to help individuals take action on climate change and (2) believed creating a MOOC was critical to career advancement. (3) The faculty member also hoped to involve students to improve their knowledge and skills, while creating a learner-centered MOOC on an ambitious timeline. Participants reported that the majority of their motivations were fulfilled and were generally satisfied with the resulting MOOC and overall co-design experience. This study offers new insights into the motivations that drive instructors to create MOOCs as well as into adopting the “student as partners” model for MOOC co-design.